2008
DOI: 10.1111/j.1365-3156.2008.02069.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia in a rural Ugandan HIV cohort: prevalence at enrolment, incidence, diagnosis and associated factors

Abstract: Summary Objectives  To determine the prevalence and incidence of anaemia in HIV‐positive and negative individuals; to identify risk factors for anaemia, prior to the introduction of HAART; and to determine the validity of the clinical diagnosis of anaemia. Methods  Between 1990 and 2003, we followed a rural population based cohort of HIV‐infected and uninfected participants. Prevalence and incidence of anaemia were determined clinically and by laboratory measurements. The sensitivity, specificity and predictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
40
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 17 publications
(25 reference statements)
18
40
4
Order By: Relevance
“…18 Lower Hb levels in HIV-infected than uninfected individuals are nearly universally observed, and our finding is similar to prior studies from sub-Saharan Africa, for example, HIV-infected women were more likely to be anaemic than HIV negative women (23.6% vs 12.8%; p=0.031) in a Ugandan study. 20 In a recent Rwandan study of 200 HIV-infected (of whom 50 were on ART) and 50 uninfected women, the prevalence of anaemia was similar to our study (29% and 8%, respectively). 23 Poor nutritional status may also cause anaemia, 17 which may be reflected in the association of anaemia with lower BMI in this urban Rwandan population.…”
Section: Discussionsupporting
confidence: 87%
“…18 Lower Hb levels in HIV-infected than uninfected individuals are nearly universally observed, and our finding is similar to prior studies from sub-Saharan Africa, for example, HIV-infected women were more likely to be anaemic than HIV negative women (23.6% vs 12.8%; p=0.031) in a Ugandan study. 20 In a recent Rwandan study of 200 HIV-infected (of whom 50 were on ART) and 50 uninfected women, the prevalence of anaemia was similar to our study (29% and 8%, respectively). 23 Poor nutritional status may also cause anaemia, 17 which may be reflected in the association of anaemia with lower BMI in this urban Rwandan population.…”
Section: Discussionsupporting
confidence: 87%
“…This study showed that 49.5% of the sample population had anaemia, which is higher than the 18.9% prevalence reported in Uganda [13] but lower than 80% obtained by Erhabor et al in Port Harcourt, Nigeria, among untreated HIV patients [14]. This study is in agreement with previous studies by Akinsegun et al [15], Zon and Groopman [7], Spivak et al [16] and a multicentre AIDS cohort study showing that anaemia was directly related to the degree of immunosupression [16].…”
Section: Discussioncontrasting
confidence: 46%
“…The HIV-infected women were particularly more likely than HIV-negative women to be anemic (23.6% and 12.8%, respectively; P = 0.031). 21 The lower percentage of anemia among HIV-negative women in our study may be related to the fact that the women coming to outpatient department of Butare University Teaching Hospital come from the urban area and have a better nutritional status than the general population.…”
Section: Discussionmentioning
confidence: 79%